The Effect of Style, Feedback, and Context on Portfolio Exploratory Behavior. Issue 3 (2nd July 2016) - Taylor, Sheridan; Taylor, Roger
ABSTRACT: This paper reports empirical evidence for the impact of investor style differences and context on exploratory behavior within the management of investment portfolios. The paper looks at the effect of short-term feedback and context on behavior and offers new perspectives on the processes by which decisions are made under conditions of rapid change and uncertainty. The results show that search behavior is affected by feedback on short-term investment returns and the volatility of those returns, conditional upon investor style and context, with considerable evidence of both reactionary behavior and avoidance within the domain of losses. No evidence is found to support the disposition effect, with investors instead found to be more likely to review and cut material losses based upon overall context. The paper briefly considers cognitive explanations for the results and examines further evidence relating to the process of decision making within complex systems, the applicability of feedback loop models, and the impact of uncertainty on choice preference.